Classicism and romanticism the sober and the sublime. (The Center for Humanities, 1987)
Shows how the movements of classicism and romanticism are expressions of man's need for form, pattern, and security, as well as his desire for change, fantasy, and feelings. Includes illustrations of works of art and excerpts from literature and music.